P-C6 tyrosine-sulfated peptides from the V2 loop of gp120 Are potent HIV-1 inhibitors. (March 2017) - Liu, Qingbo; Cimbro, Raffaello; Zhang, Peng; Dolan, Michael; Lusso, Paolo
Abstract : The second variable (V2) loop of HIV-1 gp120 is the focus of increasing attention both as a functional domain and as a vaccine target. Recently, we identified two tyrosine sulfation sites in this region that may help to stabilize the envelope trimer in a native state through intramolecular interaction with V3 base. To further investigate the functional role of this region and its potential usefulness as a template for the design of new HIV-1 inhibitors, we created tyrosine-sulfated peptides based on the V2 sequence and showed that they efficiently bind to both monomeric and trimeric gp120 in a CD4-dependent manner. Furthermore, tyrosine-sulfated V2 peptides, but not their unsulfated counterpart, potently inhibit HIV-1 entry and fusion by preventing coreceptor utilization, with the highly conserved C-terminal sulfotyrosine, Tys177, playing a dominant role. Unlike CCR5 N-terminus-derived sulfated peptides, we found that V2 peptides inhibit a broad range of HIV-1 isolates irrespective of their coreceptor tropism. Due to their potency, specificity and breadth of antiviral activity, sulfated V2 peptides may represent promising candidates for the design of new HIV-1 entry inhibitors.